2016
DOI: 10.30699/jidai.29.2.57
|View full text |Cite
|
Sign up to set email alerts
|

Fracture Strength of Severely Damaged Primary Anterior Teeth after Restoration with Composite Resin and Resin-Modified Glass Ionomer Cement

Abstract: Background and Aim: Restoration of primary anterior teeth with severe caries extending to the gingival margin is challenging for many clinicians especially in uncooperative children. Resin modified glass ionomer cements (RMGICs) can be suitable for use in such cases since they require fewer application steps than composite resins. This study aimed to assess the fracture strength of severely damaged primary anterior teeth after their coronal build-up using RMGIC and composite resin. Materials and Methods: This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Evidence shows that packing the composite into the canal and creating a short composite post is among the simplest and most-effective methods suggested for restoration of severely damaged primary anterior teeth [27]. Thus, we packed the composite into the canal for coronal restoration of teeth in our study.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Evidence shows that packing the composite into the canal and creating a short composite post is among the simplest and most-effective methods suggested for restoration of severely damaged primary anterior teeth [27]. Thus, we packed the composite into the canal for coronal restoration of teeth in our study.…”
Section: Discussionmentioning
confidence: 99%
“…They stated that use of intracanal post is imperative for composite restoration of severely damaged teeth when the remaining tooth structure is not sufficient to provide adequate retention. Paryab et al [27] compared the fracture strength of composite and resin-modified glass ionomer cement for coronal restoration of severely damaged primary anterior teeth (intracanal post and coronal build-up) and found no significant difference between the two groups. However, the fracture strength of conventional composite in our study was higher than the reported value in their study (14.5 MPa versus 5.03 MPa).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Compomers may be a choice instead of other restorative materials for primary dentition for class I and II cavities [12], [13]. Class III cavities or aproximal restorations of primary incisors are often prepared with a labial or lingual access, to include a bigger surface for better adhesion and improving the longevity of the restorations [14]. Cavities and fillings in the cervix region from class V of primary incisors are similar to the ones in permanent dentition [3].…”
Section: Introductionmentioning
confidence: 99%